The Stoic Theory of Beauty (2020)
Highlights the important contribution Stoic philosophy made to aesthetics Shows that this is a largely unexplored area of interest to scholars of both ancient philosophy and aesthetics Analyses material to show that there is a coherent and substantial attempt at systematic enquiry into aesthetic phenomena Discusses how Stoic ideas could enhance our understanding of ancient aesthetics and even contribute to contemporary aesthetics Aistė Čelkytė shows us that Stoic views about beauty were substantial and compelling. She examines the ways in which the Stoics used aesthetic vocabulary in their arguments to demonstrate that aesthetic concepts played an important role in their philosophy. Čelkytė argues that understanding the Stoic’s aesthetic views allows us to interpret their famous account of virtue more thoroughly. She also explores the place that Stoic aesthetics has within the broader ancient Greek and Roman tradition, highlighting the value of incorporating Stoic views in the discussions of aesthetic properties and values.